2014
DOI: 10.15517/rbt.v62i0.16342
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between vertical distribution and carrier frequency, and preference for open spaces in arboreal katydids that use extreme ultrasound, in Gorgona, Colombia (Orthoptera: Tettigoniidae)

Abstract: Male Tettigoniidae emit sound to attract conspecific females. The sound is produced by stridulation. During stridulation the forewings open and close, but it is during the closing stroke that the scraper contacts the file teeth to generate the predominant sound components, which are amplified by adjacent wing cells specialized in sound radiation. The sounds usually exceed the sonic boundary and might occur above 40 kHz, reaching extreme ultrasonic frequencies of 150kHz in some species. Here we test the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…In addition, we explored the relationship of acoustic activity of each species with environmental variables extracted from satellite remote sensing data. We experienced difficulties in collecting canopy dwellers, for which we recommend the use of specialized methods such as fogging ( Montealegre-Z et al, 2014 ), light trapping ( e.g ., Symes et al, 2021 ), or specialized manual tracking ( Diwakar & Balakrishnan, 2007b ) for future studies. As studies on environmental effects on insect acoustic communities are still rare, our study is an important precedent, and serves as a good example on how satellite remote sensing data can be used along with acoustic monitoring schemes in areas with low accessibility to ground-based methods of environmental measurement, such as weather stations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we explored the relationship of acoustic activity of each species with environmental variables extracted from satellite remote sensing data. We experienced difficulties in collecting canopy dwellers, for which we recommend the use of specialized methods such as fogging ( Montealegre-Z et al, 2014 ), light trapping ( e.g ., Symes et al, 2021 ), or specialized manual tracking ( Diwakar & Balakrishnan, 2007b ) for future studies. As studies on environmental effects on insect acoustic communities are still rare, our study is an important precedent, and serves as a good example on how satellite remote sensing data can be used along with acoustic monitoring schemes in areas with low accessibility to ground-based methods of environmental measurement, such as weather stations.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2-year study of the diet of a gleaning bat species in Panama, Belwood [52] found that C. wheeleri formed the largest proportion of katydids in the diet (23%). Pseudophylline katydids are the most common subfamily of katydid found in gleaning bat diets [28,33,52] and often inhabit the forest understorey (less than 10 m [71]), a common hunting location for eavesdropping bats [72,73]. For these reasons, pseudophylline katydid species might be more likely to respond to the calls of bats than phaneropterine katydids, even if the calls do not correlate well with danger.…”
Section: Discussionmentioning
confidence: 99%
“…Neotropical katydids have evolved sophisticated auditory features as strategies for survival against substrate gleaning bats 6165 . The habitat of C. gorgonensis is in cluttered vegetation of the tropical forest understory 66 . In this environment, acoustic signals are heavily attenuated which leads to significant transmission loss 41,67 , but insects have evolved sophisticated receivers to perform call discrimination in these acoustically challenging environments 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Neotropical katydids have evolved sophisticated auditory features as strategies for survival against substrate gleaning bats (Belwood, 1990;Belwood and Morris, 1987;Nickle and Castner, 1995;ter Hofstede et al, 2017ter Hofstede et al, , 2010. The habitat of C. gorgonensis is in cluttered vegetation of the tropical forest understory (Montealegre-Z et al, 2014). In this environment, acoustic signals are heavily attenuated which leads to significant transmission loss (Rheinlaender and Römer, 1986;Wiley and Richards, 1978).…”
Section: Bat Detection By Resonancementioning
confidence: 99%